PERCEPTION OF FEMALE STUDENTS OF KING SAUD UNIVERSITY TOWARDS PREMARITAL SCREENING - Alam, Awatif A. (Medknow Publications & Media Pvt Ltd, 2006)
OBJECTIVES: The aim of this study was to investigate the perception of King Saud University female students towards the implementation of premarital screening (PMS) in the Kingdom of Saudi Arabia (KSA). METHODS: Two consecutive surveys on knowledge, attitudes and practice (KAP) were conducted two and nine months after the compulsory implementation of PMS in KSA in 1/1/1425H. The female students of King Saud University were given health education lectures before the survey. The first survey was done with a designed close-ended questionnaire distributed at pre and post stages of the health education lecture. However, the second one explored the participants’ perception of the same items in open-ended questions summarized as a “consensus statement”. In fulfillment of their demands, the signed statement was mailed to the legislative authorities. RESULTS AND DISCUSSION: A total of 140 university female students attended the first lecture. The response rate for both pre and post lecture surveys were 132 (94.3%) and 128 (91.4%) respectively. A total of 112 out of 132 (84.8%) students in the pre test and 111 out of 128 (86.7%) in the post-test were single. Of the married students 7/20 (35.0%) and 7/17 (41.2%) in pre and post tests had previously had PMS screening. The attitude of the students towards PMS was generally positive. One hundred and eight (81.8%) in the pre test and 110 (85.9%) in the post test saw the importance of PMS in controlling the commonest hereditary diseases. However, a smaller percentage of students (69.7% and 75.0%) in pre and post lecture respectively were in favor of the compulsory application of PMS in KSA. In spite of the positive attitude of all the students in the pre and post tests, fears were expressed towards the confidentiality of PMS test results and it was felt that social and psychological problems would ensue from abnormal results. This, however, does not represent the feeling of the entire population in KSA since the participants of the study formed a select group. The second awareness lecture was attended by 319 students from the College of Education. They were subsequently requested to state their perceptions of PMS application with regard to its content, nature and method of application in KSA in their own words. The collected forms were summarized into a “consensus statement” and signed by all 319 students. They felt that the scope of PMS should be extended to investigate and screen for other diseases especially sexually transmitted diseases that would adversely affect the health of members of the family and the community as a whole. Their worry about the lack of screening for other diseases may be because a majority of the study group were single and would, therefore, refuse to get married on account of the risks to their future offspring. In addition, it may reflect their knowledge of the effects of globalization on the transmission of diseases. CONCLUSIONS: Health education is an important means of improving the public's perception of newly-introduced health interventions. University students have a good perception of the compulsory implementation of PMS in KSA. Pre-marital screening could be extended to include a broader spectrum of health/genetic disorders and will be useful for early identification and possible intervention as well as the prevention of complications.